2002
DOI: 10.1093/hmg/11.9.1119
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the LGI1/Epitempin gene on 10q24 cause autosomal dominant lateral temporal epilepsy

Abstract: Autosomal dominant lateral temporal epilepsy (EPT; OMIM 600512) is a form of epilepsy characterized by partial seizures, usually preceded by auditory signs. The gene for this disorder has been mapped by linkage studies to chromosomal region 10q24. Here we show that mutations in the LGI1 gene segregate with EPT in two families affected by this disorder. Both mutations introduce premature stop codons and thus prevent the production of the full-length protein from the affected allele. By immunohistochemical studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
229
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(236 citation statements)
references
References 16 publications
4
229
0
3
Order By: Relevance
“…Interestingly, further evidence for the disease relevance of these proteins come from known genetic variations. Human LGI1-mutations produce a lateral temporal lobe epilepsy syndrome 17 and mice lacking LGI1 show a variety of motor semiologies 18 . Humans with CASPR2 mutations present autism, seizures, and peripheral neuropathy 19 .…”
Section: The Vgkc-complex: Lgi1 Caspr2 and Contactin-2mentioning
confidence: 99%
“…Interestingly, further evidence for the disease relevance of these proteins come from known genetic variations. Human LGI1-mutations produce a lateral temporal lobe epilepsy syndrome 17 and mice lacking LGI1 show a variety of motor semiologies 18 . Humans with CASPR2 mutations present autism, seizures, and peripheral neuropathy 19 .…”
Section: The Vgkc-complex: Lgi1 Caspr2 and Contactin-2mentioning
confidence: 99%
“…Although a single transmembrane domain was initially predicted in its central part [Chernova et al, 1998], the Lgi1 protein does not contain any transmembrane domain and is therefore thought to be secreted [Morante-Redolat et al, 2002;Staub et al, 2002]. This view is supported by in vitro experiments that have shown that the Lgi1 protein produced by transfected cells is secreted into the cell medium [Furlan et al, 2006;Senechal et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…In both tissues, two mRNA isoforms resulting from alternative splicing are present: a fulllength 2254-bp transcript, which is more abundantly expressed in the brain, and a shorter splice isoform of 1456 bp, encompassing the 5 0 half of the full-length coding region, which is expressed at lower levels [Chernova et al, 1998;Morante-Redolat et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Its inheritance pattern is autosomal dominant with reduced penetrance (around 70%). Mutations associated with ADLTE are found in leucine-rich, glioma inactivated 1 (LGI1 [MIM: 604619]) [4][5][6] in 30%-50% of ADLTE-affected families. 3,7,8 Other genes harboring ADLTE-causing mutations are unknown.…”
mentioning
confidence: 99%